Patient-derived acellular ascites ﬂuid affects drugresponses in ovarian cancer cell lines through theactivation of key signalling pathways - Bischof, Katharina; Cremaschi, Andrea; Eroukhmanoff, Lena; Landskron, Johannes; Flage-Larsen, Lise-Lotte; Gade, Alexandra; Bjørge, Line; Urbanucci, Alfonso; Taskén, Kjetil (Wiley, 2024)
Malignant ascites is commonly produced in advanced epithelial ovarian cancer (EOC) and serves as unique microenvironment for tumour cells. Acellular ascites fluid (AAF) is rich in signalling molecules and has been proposed to play a role in the induction of chemoresistance. Through in vitro testing of drug sensitivity and by assessing intracellular phosphorylation status in response to mono- and combination treatment of five EOC cell lines after incubation with AAFs derived from 20 different patients, we investigated the chemoresistance-inducing potential of ascites. We show that the addition of AAFs to the culture media of EOC cell lines has the potential to induce resistance to standard-of-care drugs (SCDs). We also show that AAFs induce time- and concentration-dependent activation of downstream signalling to signal transducer and activator of transcription 3 (STAT3), and concomitantly altered phosphorylation of mitogen-activated protein kinase kinase (MEK), phosphoinositide 3-kinase (PI3K)–protein kinase B (AKT) and nuclear factor NF-kappa-B (NFκB). Antibodies targeting the interleukin-6 receptor (IL6R) effectively blocked phosphorylation of STAT3 and STAT1. Treatments with SCDs were effective in reducing cell viability in only a third of 30 clinically relevant conditions examined, defined as combinations of drugs, different cell lines and AAFs. Combinations of SCDs and novel therapeutics such as trametinib, fludarabine or rapamycin were superior in another third. Notably, we could nominate effective treatment combinations in almost all conditions except in 4 out of 30 conditions, in which trametinib or fludarabine showed higher efficacy alone. Taken together, our study underscores the importance of the molecular characterisation of individual patients' AAFs and the impact on treatment resistance as providing clinically meaningful information for future precision treatment approaches in EOC.
Keywords: 32 Ciencias Médicas ::3201 Ciencias clínicas::3201.01 Oncología; ODS 3 - Salud y bienestar